The weirn books. 1, Be wary of the silent woods - Chmakova, Svetlana, 1979- (JY, 2020)
Ailis and Na'ya are weirns, witches who have a demon guardian, and attend a school for supernatural creatures like witches, vampires, and shifters. When mysterious events start happening and Na'ya's brother, D'esh, goes missing, the two girls have to solve the mystery and find D'esh.